Hajj Pillars Education Application Using Markerless Augmented Reality Method - Eka Fatra Arif Hidayatullah; Rohman Dijaya; Nuril Lutvi Azizah (Procedia of Engineering and Life Science, 2022)
Hajj is a special worship, which is a dream and obligation for Muslims in the world to perform it, for those who are physically and materially capable. An introduction to the pilgrimage has been obtained since the 3rd grade of Elementary School (SD). The long process of the pilgrimage with various pillars and provisions contained in the procedures for its implementation often raises the disinterest of students in learning to understand and study the pilgrimage more deeply. To achieve the desired competence, many learning media have been developed, one of which is Augmented Reality (AR) technology. Augmented Reality (AR) is a technology that allows you to integrate 3D objects into a real environment. Based on this problem, the author makes an application about the introduction and pillars of the pilgrimage based on Augmented Reality using the Markerless method. Making applications using Blender software as a modeler and Unity 3D as an application maker. It is hoped that this application can introduce Augmented Reality into the world of education, and help students, especially elementary school children, get to know the pillars of Hajj better.